ANALISIS PENGARUH JENIS NYERI DADA TERHADAP RATA-RATA TEKANAN DARAH DAN USIA MENGGUNAKAN MANOVA - Helvy Tiana Rosa Nabila; Annisa’ Riskika Hayyu; Sri Pingit Wulandari (Merwin Publisher, 2024)
This study aims to analyze the effect of chest pain type on mean blood pressure and age using the Multivariate Analysis of Variance (MANOVA) method. Chest pain is a common symptom that can indicate various health conditions, including heart disease. The data used in this study was taken from the